PENGARUH LAMA WAKTU PEREBUSAN BIJI LABU KUNING TERHADAP SIFAT SENSORI DAN AKTIVITAS ANTIOKSIDAN PADA MINUMAN FERMENTASI YOGHURT BOILING TIME EFFECT OF PUMPKIN SEEDS ON SENSORY PROPERTIES AND ANTIOXIDANT ACTIVITY IN FERMENTED YOGHURT DRINKS - Zakaria, Denny; Zuidar, Ahmad Sapta; Sartika, Dewi; Yuliana, Neti (Jurnal Agroindustri Berkelanjutan, 2023)
The purpose of this study was to determine the effect of boiling pumpkin seeds on the sensory properties and antioxidant activity of yoghurt.  The study was structured using a 4 × 4 Latin Rectangle Design (RBSL) with a factor of boiling time of pumpkin seeds as much as 4 treatment levels, 4 minutes (A), 5 minutes (B), 6 minutes (C), and 7 minutes (D).  The data tested for similarity of variance using the Bartlett test and additional data were tested with the Tuckey test. Data analysis of variance was carried out to obtain an estimator of the error variance and determine the effect between treatments.  The analysis was continued by using the Least Significant Difference (LSD) test at the 5% and 1% significance levels. The results showed that the boiling time of pumpkin seeds did not significantly affect the sensory properties of the texture with a value of (4.07-4.15), thick, aroma with a value of (4.07-4.13) yogurt scent, colour with a value of (3.08-3.19) slightly greenish, taste with a value of (4.05-4.22) sour, overall acceptance with a value of (3.7-3.95) which is slightly like, and antioxidant activity of yogurt with a value of (40 .3%-45.3%.). The antioxidant activity of yogurt with the addition of pumpkin seed extract has a higher value of 45,31% compared to the antioxidant activity of plain yogurt, which is 28,49%.  Based on these results, the conclusion was that the boiling time of 4, 5, 6, and 7 minutes had no effect on the sensory properties and antioxidant activity of yogurt with the addition of pumpkin seed extract.